Integration of social spatial data to assess conservation opportunities and priorities. (August 2019) - Brown, Greg; McAlpine, Clive; Rhodes, Jonathan; Lunney, Daniel; Goldingay, Ross; Fielding, Kelly; Hetherington, Scott; Hopkins, Marama; Manning, Clare; Wood, Matthew; Brace, Angie; Vass, Lorraine; et al.
Abstract: Effective wildlife conservation requires consideration of ecological and social factors, including social acceptability of conservation actions. Using the threatened koala ( Phascolarctos cinereus ) as a case study, we demonstrate a novel, socio-ecological approach for identifying conservation opportunity that spatially connects landscapes with community preferences to prioritize koala recovery strategies at a regional scale. We conceptualize conservation opportunity as the spatial integration of three sustainability criteria— ecological potential, social acceptability, and economic feasibility . The social acceptability criterion was assessed using a crowdsourced spatial survey that identified spatial preferences for koalas and land uses that impact koala conservation. As a novel approach, we addressed important research questions regarding the design, collection, and analysis of crowdsourced mapping data for identifying socially acceptable conservation opportunities. Public preferences for koalas were mapped closer to home, in higher suitable koala habitats than expected, were more pronounced in conservation and natural areas on public lands, and were mapped less frequently in modified agricultural landscapes. When the multiple criteria ( ecological, social, and economic ) were included in the conservation assessment, we found the social acceptability criterion exerted the greatest influence on spatial conservation priorities. The systematic assessment of social criteria for conservation using spatial surveys provides information that can be integrated with ecological information to prioritize conservation opportunities. Potential enhancements include expanding survey recruitment efforts and using alternative social data collection methods to achieve greater geographic and socio-demographic representation, and augmenting the economic feasibility assessment with private property values and transaction data from voluntary conservation agreements with private landowners. Highlights: Defines conservation opportunity as convergence of ecological, social, economic criteria Implemented spatial survey to identify social acceptability (preferences) for koala conservation Public preferences mapped close to home, in higher suitable habitat, and more on public lands. Social acceptability criterion had greatest influence on conservation options. Method can be used to prioritize investment in private land conservation.